Aplikasi Pencarian Dengan Menggunakan Algoritma Knuth Morris Pratt Pada Berkas Dokumen Shipment - Rusito Rusito; Nurul Khasanah (STMIK Budi Darma, 2019)
File search of shipment transactions is vital for a company engaged in export import. If the file is lost or tucked or exchanged, the export and import management cannot be completed on time. The system that has been running in the search for files is still manual by searching for files in physical form in file file cabinets or searching for pdf attachments found in e-mail. With the new file search system, it is expected to save search time and overcome existing problems. This system was developed with ASP.net MVC programming language and SQLite database by applying the Knuth Morris Pratt algorithm. From the results of the effectiveness test, it can be concluded that the effectiveness of the new system is far greater than the old system, which is equal to 85.00%. While for the old system only 45.00%. This shows that the new system is better and more effective than the old system.